Elevated prevalence of antisocial behavior in adolescent children whose mothers misuse opioids. (1st October 2020) - Feder, Kenneth A.; Ali, Mir M.; Sherman, Laura J.; Letourneau, Elizabeth; Barry, Colleen L.; Stuart, Elizabeth A.; Mutter, Ryan
Highlights: Maternal opioid use associated with 60 % higher odds of antisocial acts by adolescent children. This increase is similar to the increase associated with other substances. Special services for mothers with opioid use disorder may benefit mothers and children. Abstract: Background: Past studies show that illicit opioid use may impair parents' ability to care for their children. However, few studies have examined adverse outcomes in adolescent children of mothers who misuse opioids. Methods: Data come from the National Survey on Drug Use and Health's nationally representative matched sample of mothers and their adolescent children who resided in the same household. The outcome of interest was whether adolescents engaged in aggressive or antisocial behaviors in the past year. Using logistic regression, adolescent children whose mothers engaged in past-year opioid misuse were respectively compared to children whose mothers used other illicit drugs, had an alcohol use disorder, or had no misuse of substances. To control for confounding, propensity scores were used to match the three other maternal substance use groups to mothers who misused opioids on a number of measured confounding variables. Results: The odds of antisocial behaviors were 1.6 times higher among adolescent children whose mother engaged in past-year opioid misuse than matched adolescent children whose mothers reported no illicit substance use. There was no significant difference in antisocial behaviors between adolescents whose mothers misused opioids and either adolescents whose mothers used illicit drugs or had an alcohol use disorder. Conclusion: As the United States seeks to respond to the needs of families impacted by its ongoing opioid crisis, it is likely that services will be needed not only for parents who misuse opioids, but also for their children, who are at elevated risk for adverse behavioral outcomes.